Assessing the Outcomes of Circular Economy and Waste Management Partnerships between Indonesia and Denmark - Ellen Dollan; Bagas Dwi Kurnia Ramadhan; Naida abrina (Pandawan Sejahtera Indonesia, 2023)
In the pursuit of sustainable environmental solutions, the bilateral collaboration between Indonesia and Denmark has emerged as a focal point of study, particularly within the spheres of the circular economy and waste management. This research, anchored in a qualitative descriptive methodology, delves deep into the intricacies of this partnership, shedding light on its commendable strides in fostering the exchange of best practices and pioneering waste reduction techniques, notably waste incineration. The collaboration, rooted in a shared commitment to environmental sustainability, has not only aimed at diminishing the adverse environmental repercussions of waste but has also sought to catalyze opportunities for both nations to achieve their waste management objectives more efficiently. However, the journey has not been devoid of challenges. A significant impediment identified is Indonesia's constrained reservoir of expert resources, which has had tangible repercussions on the effective implementation and scaling of circular economy initiatives. This limitation underscores a broader challenge faced by many emerging nations, emphasizing the critical need for capacity building and resource augmentation. The research's implications are manifold, extending beyond policy formulation to influence practitioners and academics in the environmental and sustainable development sectors. By offering a nuanced perspective on the dynamics of international collaborations, the study underscores the potential and challenges of such partnerships in addressing pressing global environmental issues, thereby serving as a beacon for similar endeavors in other developing contexts.